1983
DOI: 10.1007/bf00294991
|View full text |Cite
|
Sign up to set email alerts
|

A developmental toxicity and psychotoxicity evaluation of FD and C Red Dye #3 (erythrosine) in rats

Abstract: Two experiments were conducted to evaluate FD and C Red Dye #3 for its developmental toxicity and psychotoxicity. Adult Sprague-Dawley rats were fed diets containing the dye for 2 weeks and were then bred. The diets were continued for the females throughout gestation and lactation and were provided continuously to their offspring thereafter. The treatment groups for Experiment 1 were Red Dye #3 as 0.0, 0.25, 0.5, or 1.0% of the diet (w/w), and a positive control group treated with the toxin hydroxyurea on days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…A number of studies have also failed to establish significant dose-related adverse effects in the reproductive toxicity and post-partum development of F0 and F1 generation of rats that received erythrosine (Vorhees et al, 1983;JECFA, 1986;Tanaka, 2001). Erythrosine has also been discovered to possess no psychotoxic potential in developing rats (Vorhees et al, 1983).…”
Section: Reproductive and Developmental Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have also failed to establish significant dose-related adverse effects in the reproductive toxicity and post-partum development of F0 and F1 generation of rats that received erythrosine (Vorhees et al, 1983;JECFA, 1986;Tanaka, 2001). Erythrosine has also been discovered to possess no psychotoxic potential in developing rats (Vorhees et al, 1983).…”
Section: Reproductive and Developmental Toxicitymentioning
confidence: 99%
“…A number of studies have also failed to establish significant dose-related adverse effects in the reproductive toxicity and post-partum development of F0 and F1 generation of rats that received erythrosine (Vorhees et al, 1983;JECFA, 1986;Tanaka, 2001). Erythrosine has also been discovered to possess no psychotoxic potential in developing rats (Vorhees et al, 1983). Erythrosine, however, was adjudged to have potential toxic effects on the reproductive process in male adult mice causing a decrease in the epididymal sperm count and motility as well as an increased frequency in sperm abnormalities (Abdel-Aziz et al, 1997;Vivekanandhi et al, 2006 …”
Section: Reproductive and Developmental Toxicitymentioning
confidence: 99%
“…Vorhees et'al. ( 1983a ) , supported in part by FDA, used hydroxyurea as a positive control in a study to evaluate postnatal developmental toxicity induced by FD&C Red Dye #3 in rats. The experiment for FD&C Red Dye #3 will not be discussed here.…”
Section: 0 Developmental Toxicity Datamentioning
confidence: 99%
“…Most of these studies involved administration on a single day of gestation or on a restricted number of days (e.g., GD 9–12), limiting their utility for an evaluation of the entire gestational period. There are two studies (Vorhees et al, 1983a, b) involving postnatal administration of hydroxyurea to developing experimental animals. There are experimental animal studies addressing mechanism of action.…”
Section: 0 Developmental Toxicity Datamentioning
confidence: 99%
“…In developmental toxicity studies, Erythrosine does not adversely affect development of young animals at dose levels up to 500 mg/kg bw/day, which is the highest dose level tested for this endpoint. There are no indications, based on the studies evaluated by JECFA and SCF, that Erythrosine can adversely affect male fertility at dose levels up to 2000 mg/kg bw/day, which is the highest dose levels tested (Albridge et al, 1981;Vorhees et al, 1983). Two more recent studies have however indicated that Erythrosine may affect testicular function.…”
mentioning
confidence: 99%